Ethics and politics: cases and comments / edited by Amy Gutmann and Dennis Thompson - "Gutmann, Amy (ed.);Thompson, Dennis (ed.)" (Singapore, 2006)
This book helps students recognize and assess the strengths and weaknesses of moral arguments in the making of public policy. Part one considers the ethics of process: the morally questionable means--violence, deception, and corruption--that are most commonly used by public officials. Part two discusses the ehics of policy: the valuable but often competing ends that public officials strive to achieve. Conflicting values, scarce resources, and stakes as high as life and death combine with the duties of public office to make choices among policy goals controversial and morally difficult. In both parts, each ethical issue is paired with case studies in contemporary American politics. For example, the decision to defend organ transplants in Arizona introduces competing theories of justice; decisions by the FDA to ban AIDS-testing at home and by the New York legislature to ban dwarf-tossing as entertainment in bars illuminate the issues of liberty, paternalism, and moralism.
Keywords: Ethics